Making every drop count: reducing wastage of a novel blood component for transfusion of trauma patients. Issue 3 (8th July 2021) - McCullagh, Josephine; Proudlove, Nathan; Tucker, Harriet; Davies, Jane; Edmondson, Dave; Lancut, Julia; Maddison, Angela; Weaver, Anne; Davenport, Ross; Green, Laura
Abstract : Recent research demonstrates that transfusing whole blood (WB=red blood cells (RBC)+plasma+platelets) rather than just RBC (which is current National Health Service (NHS) practice) may improve outcomes for major trauma patients. As part of a programme to investigate provision of WB, NHS Blood and Transplant undertook a 2-year feasibility study to supply the Royal London Hospital (RLH) with (group O negative, 'O neg') leucodepleted red cell and plasma (LD-RCP) for transfusion of trauma patients with major haemorrhage in prehospital settings. Incidents requiring such prehospital transfusion occur randomly, with very high variation. Availability is critical, but O neg LD-RCP is a scarce resource and has a limited shelf life (14 days) after which it must be disposed of. The consequences of wastage are the opportunity cost of loss of overall treatment capacity across the NHS and reputational damage. The context was this feasibility study, set up to assess deliverability to RLH and subsequent wastage levels. Within this, we conducted a quality improvement project, which aimed to reduce the wastage of LD-RCP to no more than 8% (ie, 1 of the 12 units delivered per week). Over this 2-year period, we reduced wastage from a weekly average of 70%–27%. This was achieved over four improvement cycles. The largest improvement came from moving near-expiry LD-RCP to the emergency department (ED) for use with their trauma patients, with subsequent improvements from embedding use in ED as routine practice, introducing a dedicated LD-RCP delivery schedule (which increased the units ≤2 days old at delivery from 42% to 83%) and aligning this delivery schedule to cover two cycles of peak demand (Fridays and Saturdays).